Faded dreams the politics and economics of race in America - Carnoy, Martin (Cambridge University Press, 1994)
Faded Dreams paints a new and challenging picture of why racial inequality changes in America. The author argues that blacks caught up with whites mainly when government policies, under political pressure by blacks and an important segment of the white community, pushed for greater racial equality. Similarly, the greatest obstacles to black gains in other periods have also been government policies. These policies usually assumed away the race problem or used it against blacks for political purposes. Faded Dreams shows that three dominant views of economic differences between blacks and whites - that blacks are individually responsible for not taking advantage of market opportunities, that the world economy has changed in ways that puts blacks at a tremendous disadvantage compared to whites, and that pervasive racism is holding blacks down - do not adequately explain why blacks made such large gains in the past and stopped making them in the 1980s and 1990s